The Influence of Digital Literacy and Learning Media Utilization on Student Learning Motivation - Kholid, Kholid; Darmawan, Didit (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
This study investigates the effect of digital literacy and learning media utilization on student learning motivation at State Junior High School 01 Tanjungbumi Bangkalan Madura. The era of globalization emphasizes the need for education that involves digital literacy and utilization of learning media to improve the quality of student learning. Learning motivation, as the key to student success, is influenced by both factors. Digital literacy affects students' access to online learning resources and plays a role in improving their learning motivation. Learning media utilization involves technology in delivering information, creating a more engaging and interactive learning experience. In this study, digital literacy and learning media utilization are identified as factors that significantly influence students' learning motivation at State Junior High School 01 Tanjungbumi Bangkalan Madura. By identifying the influence of each factor, this study provides in-depth insight into the importance of integrating digital literacy and learning media to improve students' learning motivation in the digital era. This research has implications for increasing student learning motivation.